DIAGNOSTIC VALUE OF pTAU AND NF-L LEVELS IN CEREBROSPINAL FLUID AND PLASMA IN PATIENTS WITH TRAUMATIC BRAIN INJURY - Stela Yancheva; Svetlozar Spasov; Georgi Pavlov; Iliya Bivolarski; Valentin Dichev; Maria Kazakova; Ivan Tsranchev (Science & Research)

(untitled)
Severe traumatic brain injury (TBI) is among the leading causes of death worldwide, and survivors often suffer permanent cognitive and neurological impairment. Early diagnosis and treatment can greatly improve outcomes and recovery. The purpose of this study is to investigate the diagnostic value of the biochemical markers pTau and NF-L in the early diagnosis of TBI in patients by analysing their concentration in cerebrospinal fluid and blood plasma. The study includes 20 cases of patients who suffered severe TBI. Within 24 hours of the injury, cerebrospinal fluid and plasma were collected and compared to identical samples obtained from a control group of 11 non-traumatic cadavers. The results from the present study show significant rise in cerebrospinal pTau and plasma NF-L levels in the control group, and insignificant rise of the levels of plasma pTau in TBI patients. In conclusion, the investigated molecules pTau and NF-L are not reliable for early diagnosis and monitoring of TBI.